Analysis of Forced Marriage as an Offense of Sexual Violence - Chandera Halim; Vincentius Patria Setyawan (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstrak Fenomena pelaksanaan perkawinan secara paksa sebagai suatu fenomena sosial telah bergulir menjadi suatu fenomena hukum. Pemaksaan perkawinan dalam perkembangannya menjadi salah satu bentuk dari tindak pidana kekerasan seksual sebagaimana diatur di dalam Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual. Artikel ini akan menganalisis tentang pemaksaan perkawinan sebagai jenis dari tindak pidana kekerasan seksual. Fokus kajiannya adalah berkaitan dengan pengertian tindak pidana pemaksaan perkawinan dan bentuk pertanggungjawaban pidana bagi pelaku tindak pidana pemaksaan perkawinan. Hasil dari penelitian ini adalah tindak pidana pemaksaan perkawinan merupakan pelanggaran dari hak asasi manusia dan sebagai salah satu bentuk tindak pidana kekerasan seksual. Kata Kunci: Pemaksaan Perkawinan; Kekerasan Seksual; Pertanggungjawaban Pidana. Abstract The phenomenon of forced marriage as a social phenomenon has turned into a legal phenomenon. In its development, forced marriage has become a form of criminal sexual violence as regulated in Law Number 12 of 2022 concerning Criminal Sexual Violence. This article will analyze forced marriage as a type of criminal act of sexual violence. The focus of the study is related to the definition of the criminal act of forced marriage and the form of criminal responsibility for perpetrators of the criminal act of forced marriage. The results of this research are that the criminal act of forced marriage is a violation of human rights and is a form of criminal sexual violence. Keywords: Forced Marriage; Sexual Violence; Criminal Liability.